2016
DOI: 10.3847/2041-8205/831/1/l4
|View full text |Cite
|
Sign up to set email alerts
|

The Pre-Penumbral Magnetic Canopy in the Solar Atmosphere

Abstract: Penumbrae are the manifestation of magnetoconvection in highly inclined (to the vertical direction) magnetic field. The penumbra of a sunspot tends to form, initially, along the arc of the umbra antipodal to the main region of flux emergence. The question of how highly inclined magnetic field can concentrate along the antipodal curves of umbrae, at least initially, remains to be answered. Previous observational studies have suggested the existence of some form of overlying magnetic canopy which acts as the pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Indeed, invoking such a mechanism able to lead to the presence of highly inclined, nearly horizontal magnetic fields, for being responsible for penumbra formation (or, conversely, decay) strengthens the argument which has been proposed in recent studies concerning the development of penumbrae and penumbral-like structures, from both the observational (see, e.g. Shimizu et al 2012;Lim et al 2013;Guglielmino et al 2014;Romano et al 2013Romano et al , 2014Zuccarello et al 2014;Jurčák et al 2014Jurčák et al , 2017Murabito et al 2017Murabito et al , 2018 and the theoretical point of view (Rempel 2012;MacTaggart et al 2016), even in absence of magnetic flux variations. In this perspective, our findings indicate that the effects of magnetic reconfiguration leading to penumbral enhancements driven by flares can extend well beyond the region around the flaring PILs.…”
Section: Changes In the Penumbraesupporting
confidence: 75%
“…Indeed, invoking such a mechanism able to lead to the presence of highly inclined, nearly horizontal magnetic fields, for being responsible for penumbra formation (or, conversely, decay) strengthens the argument which has been proposed in recent studies concerning the development of penumbrae and penumbral-like structures, from both the observational (see, e.g. Shimizu et al 2012;Lim et al 2013;Guglielmino et al 2014;Romano et al 2013Romano et al , 2014Zuccarello et al 2014;Jurčák et al 2014Jurčák et al , 2017Murabito et al 2017Murabito et al , 2018 and the theoretical point of view (Rempel 2012;MacTaggart et al 2016), even in absence of magnetic flux variations. In this perspective, our findings indicate that the effects of magnetic reconfiguration leading to penumbral enhancements driven by flares can extend well beyond the region around the flaring PILs.…”
Section: Changes In the Penumbraesupporting
confidence: 75%
“…Such a mechanism has been invoked to explain the formation of regular penumbrae in sunspot (Shimizu et al 2012;Romano et al 2013Romano et al , 2014, also when the penumbra formation occurs in the region of ongoing flux emergence (Murabito et al 2017(Murabito et al , 2018, as confirmed by numerical simulations (e.g. Rempel 2012;MacTaggart et al 2016). Moreover, it seems to account for the formation of other penumbral-like structures, such as orphan penumbrae, when the emerging flux is overarched by an overlying canopy (Lim et al 2013;Guglielmino et al 2014;Zuccarello et al 2014), but also when they appear as photospheric manifestations of flux ropes trapped highly in the photosphere, corresponding to chromospheric filaments (e.g., Kuckein et al 2012a,b;Buehler et al 2016).…”
Section: Discussionmentioning
confidence: 94%
“…They thought the chromospheric threads represent the pre-existing chromospheric horizontal field during the formation of penumbra filaments and suggested the emerging flux is trapped at the photosphere by the overlying chromospheric canopy fields. The presence of magnetic canopy fields in the chromosphere before penumbra formation may be crucial for the development of penumbra evidenced by chromospheric observations (Romano et al 2013(Romano et al , 2014Guglielmino et al 2014) and simulations (Rempel 2011(Rempel , 2012MacTaggart et al 2016). However, not all events of penumbral formation is accompanied with the overlying magnetic field before their formation.…”
Section: Introductionmentioning
confidence: 98%